2021
DOI: 10.1002/ppul.25388
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four‐hour pretreatment with low dose (0.25 mg/kg/dose) versus high dose (0.5 mg/kg/dose) dexamethasone in reducing the risk of postextubation airway obstruction in children: A randomized open‐label noninferiority trial

Abstract: Objective: Multidose dexamethasone pretreatment reduces risk of postextubation airway obstruction (PEAO). However, its optimal dose is not known. We planned to compare 24 h pretreatment with low-dose dexamethasone (LDD) (0.25 mg/kg/dose) versus high-dose dexamethasone (HDD) (0.5 mg/kg/dose) in reducing risk of PEAO.Design: Stratified (for age and intubation duration) randomized open-label noninferiority trial.Setting: Fifteen-bed pediatric intensive care unit in a lower-middle-income country.Patients: Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…The rate of PEAO (15%) in the index study was within the range of the documented rates of PEAO among critically ill children (18–40%) ( 20 , 23 , 27 29 ). However, the rate of PEAO in index study was lower than the reported rates of PEAO in the recent studies from our unit (32.8–34%) ( 21 , 23 ). The lower rate of PEAO could be due to the fact that we used micro-cuffed endotracheal tubes (high-volume-low-pressure) in all cases as these were routinely available from the hospital supply during the study period.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The rate of PEAO (15%) in the index study was within the range of the documented rates of PEAO among critically ill children (18–40%) ( 20 , 23 , 27 29 ). However, the rate of PEAO in index study was lower than the reported rates of PEAO in the recent studies from our unit (32.8–34%) ( 21 , 23 ). The lower rate of PEAO could be due to the fact that we used micro-cuffed endotracheal tubes (high-volume-low-pressure) in all cases as these were routinely available from the hospital supply during the study period.…”
Section: Discussioncontrasting
confidence: 85%
“…Enteral feeding was started as soon as possible, preferably within 24 h of admission to the PICU. Among children intubated for >48 h, six dosage of dexamethasone (0.5 mg/kg/dose) were used peri-extubation, with first dose given 24 h prior to extubation ( 20 , 21 ). Feeding was withheld for 6 h prior to extubation and 4–6 h after extubation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal dosing also remains uncertain, with at least one study suggesting noninferiority of a dose of 0.25 mg/kg administered fourth hourly for 24 h prior to extubation when compared to 0.5 mg/kg. 22…”
Section: F I G U R E 1 (A) Cognitive Aid For R2d2 Extubation Planner ...mentioning
confidence: 99%
“…Unlike in adults, systematic reviews in neonatal and pediatric settings have suggested that there is not enough evidence to make strong recommendations regarding their efficacy in reducing postextubation complications 19,20 . A more recent study suggests there may be some reduction in postextubation issues if steroids are administered for 24 h prior to extubation, rather than only 6 h 21 . In this publication, the authors suggested particular utility in high‐risk children intubated for over 48 h. In the setting of ventilation for over 48 h, prior treatment with corticosteroids is a reasonable measure if there are no contraindications to steroid administration.…”
Section: The Space For Better Planningmentioning
confidence: 99%